MicroRNA regulation of the bovine alveolar macrophage response to Mycobacterium bovis - Vegh, Peter (Trinity College (Dublin, Ireland). Department of Genetics, 2015)
Bovine tuberculosis is one of the most economically significant infectious diseases of cattle in Ireland and globally, resulting in economic losses of approximately €2 billion annually. The causative agent is Mycobacterium bovis, a rod-shaped, Gram positive, acid-fast bacterium that is a member of the Mycobacterium tuberculosis complex (MTBC), a group of highly related pathogens that are spread via an airborne route.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin